40 W Continuous Wave Ce:Nd:YAG Solar Laser through a Fused Silica Light Guide - Almeida, Joana (2022)
Funding: This research was financially supported by Science and Technology Foundation of Portuguese Ministry of Science, Technology and Higher Education (FCT-MCTES) in the framework of the strategic project and the exploratory research project EXPL/FIS-OTI/0332/2021. The solar laser research was also supported by the Solar Facilities for European Research Area–Third Phase (SFERA III), Grant Agreement No. 823802. Funding Information: Acknowledgments: The authors express their gratitude for the FCT-MCTES fellowship grants CEECIND/03081/2017, PD/BD/142827/2018, PD/BD/128267/2016, 2021.06172.BD, SFRH/BD/ 145322/2019 and SFRH/BPD/125116/2016. Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.